Self-Control and the Phenomenon of Toxic Online Disinhibition in Teenagers Who Have Twitter - Ramadhani, Annisa Zahra; Merida, Sarita Candra (Utan Kayu Publishing, 2024)
This study explores the significant negative correlation between self-control and toxic online disinhibition behaviors among adolescents on Twitter, utilizing a quantitative correlational methodology. The research focused on a purposively sampled group of 165 teenagers, aged 12-21, in Bekasi City who actively use Twitter. This selection was driven by the desire to understand social media behaviors among urban youth, with non-probability sampling allowing for targeted data collection from this specific demographic. The research instruments included a Likert scale to measure both self-control and the levels of toxic online disinhibition. Spearman correlation analysis revealed that higher self-control is associated with lower levels of toxic online disinhibition, indicating a moderate negative relationship. These findings underscore the importance of interventions aimed at enhancing self-regulatory skills among teenagers to mitigate negative online behaviors. Further research could incorporate mediating factors such as emotional intelligence and socio-environmental influences to enrich understanding of these dynamics. The results contribute to the existing literature by highlighting the potential of targeted educational policies in fostering more positive online interactions among youth.